Eucalyptus robusta leaves methanolic extract suppresses inflammatory mediators by specifically targeting TLR4/TLR9, MPO, COX2, iNOS and inflammatory cytokines in experimentally-induced endometritis in rats. (1st March 2018) - Tiwari, Aastha; Singh, Preeti; Jaitley, Pooja; Sharma, Sushant; Prakash, Atul; Mandil, Rajesh; Choudhury, Soumen; Gangwar, Neeraj Kumar; Garg, Satish K.
Abstract: Ethnopharmacological relevance: Bacterial endometritis is one of the major causes of reproductive disorders including infertility in farm animals. Antibiotics are generally used for treatment of such disorders but now a days residues of antibiotics are of great public health concern, therefore, phytoremediation is being considered as an alternative to use of antibiotics. Aim of the study: Present study was undertaken to investigate the efficacy of Eucalyptus robusta leaves methanolic extract against endometritis along with the possible mechanism of action especially targeting inflammatory biomarkers. Materials and methods: Bacterial endometritis was produced using clinical isolates of E. coli and Staphyloccocus aureus from bovines (cows and buffaloes) endometritis cases. After seven days of inoculation of the mixed bacterial culture, endometritis was confirmed based on the presence of visible pus and edema, thinning of endometrial lining and presence of large number of polymorphonuclear cells and bacterial load in uterine flushing. Female Wistar rats were divided in to five groups namely control, sham-operated, endometritis, endometritis plus Eucalyptus leaves extract and endometritis plus cefixime. Serum specific inflammatory biomarkers (interleukin-1β, interleukin-10, tumor necrosis factor-α, intercellular adhesion molecule-1, serum amyloid A) and myleoperoxidase, toll like receptors-4 and -9, inducible nitric oxide synthase, nitric oxide, cyclooxygenase 1 and 2 were estimated in uterine tissues using ELISA kits. Results: Interleukin-10, serum amyloid A, myleoperoxidase, toll like receptors-4 and-9, cyclooxygenase-2, inducible nitric oxide synthase and nitric oxide were significantly increased while non significant increase in interleukin-1β, cycloxygenase-1 and intercellular adhesion molecule-1 were observed but level of tumor necrosis factor-α was found decreased in rats of endometritis group. Histopathological lesions in uterus showed efficient induction of endometritis by presence of inflammatory cells which are lessened effectively after treatment with Eucalyptus leaves extract. Eucalyptus robusta leaves extract produced curative and protective effect against endometritis and results were comparable to or even better than cefixime. Conclusions: Eucalyptus robusta leaves extract possess promising antibacterial activity and efficacy against experimental endometritis and, therefore, holds promising potential for development of effective formulation for treatment of endometritis in animals. Graphical abstract: